ANALISIS PEMBERDAYAAN UMKM SLIPPER SAWAHAN - Tyas, Ghevira; Charissa, Chiquita; Kamila, Tiara; Fitriyani, Ayu; Karamoy, Tesalonika Claudia; Aulia, Viviana (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This analysis aims to determine the planning needed to set up a craft business and the business feasibility of KUB Mampu Jaya. The joint business group in the hotel slipper sector is a collective initiative that aims to produce and distribute slippers (slippers) specifically for hotels. With the development of the hotel industry, the demand for quality and comfortable hotel slippers continues to increase. This collaborative group of companies was created to meet these needs through the collaboration of various parties with diverse resources and expertise. The main objective of KUB Mampu Jaya is to increase the production and marketing efficiency of hotel slippers, ensure high product quality, and increase competitiveness in the market. In addition, KUB Mampu Jaya empowers local communities by creating jobs and new business opportunities. KUB Mampu Jaya uses a collaborative approach where each member contributes according to their expertise and resources. The production process involves several stages, starting from design, material selection, production, to distribution. Modern and environmentally friendly production technology is used to ensure product quality and sustainability.